2023
DOI: 10.1186/s43141-023-00569-8
|View full text |Cite
|
Sign up to set email alerts
|

A computational simulation appraisal of banana lectin as a potential anti-SARS-CoV-2 candidate by targeting the receptor-binding domain

Sofia Safitri Hessel,
Fenny Martha Dwivany,
Ima Mulyama Zainuddin
et al.

Abstract: Background The ongoing concern surrounding coronavirus disease 2019 (COVID-19) primarily stems from continuous mutations in the genome of the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), leading to the emergence of numerous variants. The receptor-binding domain (RBD) in the S1 subunit of the S protein of the virus plays a crucial role in recognizing the host’s angiotensin-converting enzyme 2 (hACE2) receptor and facilitating cell membrane fusion processes, making it a potential… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 81 publications
0
1
0
Order By: Relevance
“…Interestingly, BanLec is known to be a mannose-specific lectin. In addition, studies have shown that BanLec can inhibit HIV-1 reverse transcriptase activity, suppress influenza viral fusion, and provide protective activity against herpes simplex virus (HSV) type 1 (108). Additionally, it has been observed to suppress cancer cell proliferation (109).…”
Section: Joint Strategies In the Design Of Both Tacas And Viruses The...mentioning
confidence: 99%
“…Interestingly, BanLec is known to be a mannose-specific lectin. In addition, studies have shown that BanLec can inhibit HIV-1 reverse transcriptase activity, suppress influenza viral fusion, and provide protective activity against herpes simplex virus (HSV) type 1 (108). Additionally, it has been observed to suppress cancer cell proliferation (109).…”
Section: Joint Strategies In the Design Of Both Tacas And Viruses The...mentioning
confidence: 99%